The attitudes, perceptions and experiences of medical school applicants following the closure of schools and cancellation of public examinations in 2020 due to the COVID-19 pandemic: a cross-sectional questionnaire study of UK medical applicants - Katherine Woolf; David Harrison; Chris McManus (BMJ Open, 2021)
Objective Describe the experiences and views of medical applicants from diverse social backgrounds following the closure of schools and universities and the cancellation of public examinations in the UK due to COVID-19.Design Cross-sectional questionnaire study, part of the longitudinal UK Medical Applicant Cohort Study (UKMACS).Setting UK medical school admissions in 2020.Participants 2887 participants completed an online questionnaire from 8 April to 22 April 2020. Eligible participants had registered to take the University Clinical Admissions Test in 2019 and agreed to be invited to take part, or had completed a previous UKMACS questionnaire, had been seriously considering applying to medicine in the UK for entry in 2020, and were UK residents.Main outcome measures Views on calculated grades, views on medical school admissions and teaching in 2020 and 2021, reported experiences of education during the national lockdown.Results Respondents were concerned about the calculated grades that replaced A-level examinations: female and Black Asian and Minority Ethnic applicants felt teachers would find it difficult to grade and rank students accurately, and applicants from non-selective state schools and living in deprived areas had concerns about the standardisation process. Calculated grades were generally not considered fair enough to use in selection, but were considered fair enough to use in combination with other measures including interview and aptitude test scores. Respondents from non-selective state (public) schools reported less access to educational resources compared with private/selective school pupils, less online teaching in real time and less time studying during lockdown.Conclusions The COVID-19 pandemic has and will have significant and long-term impacts on the selection, education and performance of our medical workforce. It is important that the views and experiences of applicants from diverse backgrounds are considered in decisions affecting their future and the future of the profession.